Prescription and use of ward‐delivered nasal high‐flow oxygen and non‐invasive ventilation for people with acute respiratory failure. - Cushnahan, Aiden; Harrison, Amelia; Buchan, Catherine; Naughton, Matthew T.; Dabscheck, Eli; Smallwood, Natasha (Internal Medicine Journal, 2026)
Nasal high‐flow therapy with oxygen entrained (HFNO) and non‐invasive ventilation (NIV) are important therapies for managing acute respiratory failure (ARF) in the ward‐based setting. The European Respiratory Society released guidelines in 2022 recommending the use of HFNO over conventional oxygen therapy and NIV in patients with hypoxic ARF. We conducted a 12‐month retrospective audit of ward‐based HFNO and NIV use at our hospital to determine prescribing practices for these therapies and to assist with the safe implementation of the recent European Respiratory Society guidelines. We found significant variation in prescribing practices for both HFNO and NIV.